Assessing the influence of the inclusion of Bacillus subtilis AQUA-GROW® as feed additive on the growth performance,feed utilization, immunological responses and body composition of the Pacific white shrimp, Litopenaeus vannamei - El-Sayed, Hemdan Eissa; Norhan H., Ahmed; Ashraf A., El-Badawi; Mohammad Bodrul, Munir; Omayma M., Abd Al-Kareem; Moaheda E., H. Eissa; Elamier H., M. Hussien; Salah, El-Sayed Sakr (John Wiley & Sons Ltd., 2022)
This study was carried out to determine the influence of four concentrations of dietary Bacillus subtilis on the growth performance, nutrient utilization, immunity and antioxidants activities, mortality rate and chemical composition of Litopenaeus vannamei. Three hundred and sixty L. vannamei (4.00g ± 0.03) were raised in 12 hapas (1 m3 each, placed in 4 ponds) equally distributed on apparently 38.5% protein and 10.5% lipid containing three concentrations (0.5, 1.0 and 1.5) g/kg of dietary B. subtilis and a non-supplemented control in triplicates. After 56 days of feeding trial, the growth performance, feed utilization, survival rate and immune parameters were significantly (P < 0.05) better in shrimp fed with dietary B.subtilis compared to the control. The higher dose of dietary B.subtilis showed the good performance of the parameters studied, but in some instances (specific growth rate, feed conversion rate, lysosomal enzyme activity, phenoloxidase activity etc.) were not significant (P < 0.05) difference. This study indicates that dietary B. subtilis based diets have a more positive influence on the growth performance, feed utilization, survival rate and immune response of L. vannamei fingerlings.